2021
DOI: 10.1038/s42003-021-02241-8
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency burst spiking in layer 5 thick-tufted pyramids of rat primary somatosensory cortex encodes exploratory touch

Abstract: Diversity of cell-types that collectively shape the cortical microcircuit ensures the necessary computational richness to orchestrate a wide variety of behaviors. The information content embedded in spiking activity of identified cell-types remain unclear to a large extent. Here, we recorded spike responses upon whisker touch of anatomically identified excitatory cell-types in primary somatosensory cortex in naive, untrained rats. We find major differences across layers and cell-types. The temporal structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 79 publications
5
21
0
Order By: Relevance
“…We however, maintained a static high-excitatory drive (2nS to 4nS) with a moderate inhibitory drive (1 nS to 2 nS) to avoid extreme shunting while still being able to elicit a response from 6-10 spines per cluster. Under such conditions, noisy membrane fluctuations resembling in vivo recordings (Jayant et al, 2019) (2 to 4 mV rms), a decrease in input resistance (mean R in = 59 ± 14 MΩ) consistent with the range obtained from whole-cell recordings from L5 neurons in the awake S1 (Zhao et al, 2016), and increased background firing rates, matching our in vivo recordings ( Figure 5D (ii) ) and in line with recent reports (de Kock et al, 2021), were observed. We created a high conductance dynamic input based on these parameters ( see Methods for details ), while holographic uncaging was performed across clustered synapses spanning a single dendrite ( Figure 5E and 5F ).…”
Section: Resultssupporting
confidence: 91%
“…We however, maintained a static high-excitatory drive (2nS to 4nS) with a moderate inhibitory drive (1 nS to 2 nS) to avoid extreme shunting while still being able to elicit a response from 6-10 spines per cluster. Under such conditions, noisy membrane fluctuations resembling in vivo recordings (Jayant et al, 2019) (2 to 4 mV rms), a decrease in input resistance (mean R in = 59 ± 14 MΩ) consistent with the range obtained from whole-cell recordings from L5 neurons in the awake S1 (Zhao et al, 2016), and increased background firing rates, matching our in vivo recordings ( Figure 5D (ii) ) and in line with recent reports (de Kock et al, 2021), were observed. We created a high conductance dynamic input based on these parameters ( see Methods for details ), while holographic uncaging was performed across clustered synapses spanning a single dendrite ( Figure 5E and 5F ).…”
Section: Resultssupporting
confidence: 91%
“…Our results provide direct experimental support that CS, and SB more generally, encode different circuit input features 38,[43][44][45][46][47][48][49][50][51] . Differential roles of SS and SB in signal transmission have been found in the mammalian neocortex 13,32 , thalamus 6,7,46 and cerebellum 9,11,52 , the fly sensory system [49][50][51] and electrosensory system of the electric fish 44,47,48 .…”
Section: Discussionsupporting
confidence: 57%
“…Differential roles of SS and SB in signal transmission have been found in the mammalian neocortex 13,32 , thalamus 6,7,46 and cerebellum 9,11,52 , the fly sensory system [49][50][51] and electrosensory system of the electric fish 44,47,48 . The prevalence of SS and SB across species and structures suggest that these two distinct spike output codes are a general property of projecting neurons, which might have arisen from the need to enhance information transmission and computational power via multiplexing and parallel coding while constraining the number of neurons and axonal wiring [43][44][45][52][53][54] .…”
Section: Discussionmentioning
confidence: 99%
“…2A). The generators of late-HFO activity are bursting pyramidal neurons in BA3B [8,9], most likely the thick tufted pyramidal neurons from layer 5b that are known to be activated by passive touch [49,50]. In fact, not only they are intrinsic bursting neurons that exhibit a bursting frequency compatible with HFO, but they also have adequate structure and geometry to be detected by EEG: they are well aligned in a parallel fashion with dendrites spreading from the lower part of layer 5 up to layer 1 on the cortical surface [51e53].…”
Section: High-frequency Responses In the S1 And M1 Are Mutually Relatedmentioning
confidence: 99%